Korean Maize Hybrids Present Significant Diversity in Fatty Acid Composition: An Investigation to Identify PUFA-Rich Hybrids for a Healthy Diet - Saini, Ramesh Kumar; Rengasamy, Kannan R. R.; Ko, Eun-Young; Kim, Jung-Tae; Keum, Young-Soo (Frontiers in Nutrition, 2020)
Precise information on the content and composition of nutritionally essential metabolites in food crops is a prerequisite for dietary recommendations and nutrient-dense food formulations. In the present study, the fatty acid profile of 21 Korean maize hybrids was analyzed by gas chromatography (GC)-mass spectrometry (MS). In the studied hybrids, linoleic acid (LA; C18:2n6c) was dominant (38.0 – 58.9%) followed by oleic (OA; C18:1n9c) (23.5 – 45.3%), palmitic (C16:0) (10.8 – 17.3%), and stearic acid (C18:0) (1.84 –3.86%). Among all the quantified fatty acids, the highest variation was recorded for LA and OA. The highest amount of LA (58.9%) and the lowest amount of OA (23.5%), and the most polyunsaturated fatty acid (PUFA)/monounsaturated fatty acid (MUFA) ratio of 2.47 was recorded in the Shingwang hybrid. The highest PUFA/saturated fatty acid (SFA) ratio of 4.04 was recorded in the Ahndaok hybrid due to the high contents LA (57.8%) and low amount of SFA. Similarly, the highest PUFA + MUFA/SFA ratio of 6.38 was recorded in the Pyeonggangok hybrid as a result of the high OA (34.6%) and LA (51.4%) contents, along with the lowest amount of SFA. Considering the high levels of MUFA and PUFA and low levels of SFA, the maize hybrids Pyeonggangok, Ahndaok, and Shingwang can be used in the preparation of a healthy diet.